Sporadic deficient mismatch repair in colorectal cancer increases the risk for non-colorectal malignancy: A European multicenter cohort study - Gkekas, Ioannis; Jan, Novotny; Kaprio, Tuomas; Beilmann-Lehtonen, Ines; Fabian, Pavel; Tavelin, Björn; Böckelman, Camilla; Edin, Sofia; Strigård, Karin; Svoboda, Tomas; Hagström, Jaana; Barsova, Lucie; et al. (Journal of surgical oncology, 2024)
BACKGROUND AND OBJECTIVES: Disparities between tumors arising via different sporadic carcinogenetic pathways have not been studied systematically. This retrospective multicenter cohort study evaluated the differences in the risk for non-colorectal malignancy between sporadic colorectal cancer (CRC) patients from different DNA mismatch repair status. METHODS: A retrospective European multicenter cohort study including in total of 1706 CRC patients treated between 1996 and 2019 in three different countries. The proficiency (pMMR) or deficiency (dMMR) of mismatch repair was determined by immunohistochemistry. Cases were analyzed for tumor BRAFV600E mutation, and BRAF mutated tumors were further analyzed for hypermethylation status in the promoter region of MLH1 to distinguish between sporadic and hereditary cases. Swedish and Finish patients were matched with their respective National Cancer Registries. For the Czech cohort, thorough scrutiny of medical files was performed to identify any non-colorectal malignancy within 20 years before or after the diagnosis of CRC. Poisson regression analysis was performed to identify the incidence rates of non-colorectal malignancies. For validation purposes, standardized incidence ratios were calculated for the Swedish cases adjusted for age, year, and sex. RESULTS: Of the 1706 CRC patients included in the analysis, 819 were female [48%], median age at surgery was 67 years [interquartile range: 60-75], and sporadic dMMR was found in 188 patients (11%). Patients with sporadic dMMR CRC had a higher incidence rate ratio (IRR) for non-colorectal malignancy before and after diagnosis compared to patients with a pMMR tumor, in both uni- (IRR = 2.49, 95% confidence interval [CI] = 1.89-3.31, p = 0.003) and multivariable analysis (IRR = 2.24, 95% CI = 1.67-3.01, p = 0.004). This association applied whether or not the non-colorectal tumor developed before or after the diagnosis of CRC in both uni- (IRR = 1.91, 95% CI = 1.28-2.98, p = 0.004), (IRR = 2.45, 95% CI = 1.72-3.49, p = 0.004) and multivariable analysis (IRR = 1.67,95% CI = 1.05-2.65, p = 0.029), (IRR = 2.35, 95% CI = 1.63-3.42, p = 0.005), respectively. CONCLUSION: In this retrospective European multicenter cohort study, patients with sporadic dMMR CRC had a higher risk for non-colorectal malignancy than those with pMMR CRC. These findings indicate the need for further studies to establish the need for and design of surveillance strategies for patients with dMMR CRC.
Keywords: Colorectal Neoplasms; Švédsko; Humans; lidé středního věku; MutL Protein Homolog 1; Proto-Oncogene Proteins B-raf; Sweden; Female; mutace; Aged; senioři; lidé; Europe; MutL homolog 1; protoonkogenní proteiny B-Raf; Follow-Up Studies; ženské pohlaví; kolorektální nádory; Male; Middle Aged; Retrospective Studies; DNA Mismatch Repair; prognóza; incidence; Incidence; oprava chybného párování bází DNA; Prognosis; retrospektivní studie; Mutation; mužské pohlaví; Evropa; následné studie